A Blow to the Eye—Post Traumatic Orbital Emphysema Associated With Blowout Fracture. (17th December 2020) - Qundos, Yousef; Thor, Andreas
A case of a blowout fracture with sever post traumatic emphysema is described in this study. The clinical presentation, diagnosis and management of orbital emphysema associated with blowout fractures are discussed, and the literature reviewed. This case highlights the importance of proper diagnostic measures and necessary treatment when dealing with orbital trauma patients. The clinical examination of motility, visual acuity and pupillary affect are primarily the most important factors of deciding suitable therapy. In an emergency, time is of the essence to reduce the risk of permanent vision loss.